Industrial digital control systems - Warwick, Kevin 1954-; Rees, D. (P. Peregrinus on behalf of the Institution of Electrical Engineers, 1988)
The book reviews developments in the following fields: digital control; digital signals and systems; process control; state-space concepts; system identification; adaptive control; multivariable control; optimal control; robot dynamic control; decoupling control; computer aided design for industrial control systems; microprocessor controllers; parallel processing; distributed digital control; artificial intelligence; microcomputer control; self-tuning control; and computer aided control system design.